Changes in the Form of Face-to-Face Rice in the Malay Community in Simpang Empat Village, North Labuhan Batu Regency - Aritonang, Dini Imelia Putri; Endrizal; Yade Surayya (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study discusses the face-to-face rice procession at the wedding party of the Malay community in Simpang Empat Village. The purpose of this study is to explain the face-to-face rice procession and the form of change in the face-to-face rice procession at the wedding feast of the Malay community in Simpang Empat Village. The research method used is qualitative research. Data collection techniques include field observations, interviews, and documentation. The theories used in this study are the theory of Tradition from Coomans and the theory of Social Change from J.L Gillin and J.P Gillin. The results of this study explain that the face-to-face rice tradition consists of a preparatory stage, then followed by an implementation stage. At the implementation stage, it begins with gathering the bride and groom, served various dishes, then begins the game of pulling flowers, looking for chicken in rice, eating and drinking together, choosing the food you like, distributing food, and finally repeating the in-laws.Along with the times, The tradition of face-to-face rice has also changed. Changes in terms of form and materials used, changes in terms of function are carried out and there are changes in the series of events of the face-to-face breastfeeding process. The cause of changes in the face-to-face rice tradition is due to technological advances, people's thinking that has begun to change, and economic factors.